Visual Images of Paul Virilio, Marshall McLuhan and Jean-Luc Nancy as a Subversive Mechanism in the Structure of the Modern World - M. A. Grigorieva (Концепт: философия, религия, культура, 2024)
The article offers an analysis of the philosophical and cultural ideas of Paul Virilio, Marshall McLuhan and Jean-Luc Nancy in relation to visual images, the accelerated rotation of which affects the perception of value systems and space. Since consciousness and thought arise in duration, under the pressure of speed, reflection is forced to give way to reflex, and in fact, to visual images as less demanding by nature to the procedures of assessment and interpretation. This makes us look at visual cultural studies as something that allows us to actualize the inevitable transformations in thinking and communication. The need for research is justified by the degree of influence of the visual with its system of symbols and signs on the social construction of ideas today. Thus, depending on the content, images can act both for the benefit of creative forces and from the position of destructive forces through images of violence, aestheticization of the disgusting and the transformation of the figure of the repulsive into the attractive. Just as the glance at the flesh, the cut and the wound on the pages of the first anatomical atlases responding to the demand of medical practice changed the perception of the pathological state of the body, the impression industry, operating inseparably from the constant image stimulation, blurs the line between the norm and deviation and leads to pathologies of thinking in terms of value systems, speed of information processing and distortion of the communication channel. The purpose of the study is to analyze visual images as tools to seduce the viewer, simplifying access to the control over their beliefs, desires and needs and, as a result, leading to the transformation of  world perceptions. In addition, the mechanisms by which visual images influence the viewer’s imagination are analyzed. The objectives of the research include the analysis of the mechanisms of visual images’ influence on the viewer’s imagination, in terms of the pressure they exert on the social fabric; an analysis of Paul Virilio's ideas regarding the dissemination of technological images and how they work in the context of architectural objects in the urban environment; identification of key positions of Marshall McLuhan linking the problem of high visual intensity with technical means of information transportation; updating Jean-Luc Nancy's thoughts on the visual image based on Nancy's approach to the symbol of the cut as a broken intimacy that betrays the state of modern society, and the ecstasy of openness that makes society overly hospitable to everything new and, accordingly, extremely vulnerable. Scientific novelty is determined by the author's interpretation of the area of convergence and intersection of time, space, technology and how they manifest themselves in images that affect almost all aspects of human experience. An important part is devoted to the relationship of the concepts of Paul Virilio, Marshall McLuhan and Jean-Luc Nancy with the dramatic events of their lives that ultimately influenced the conclusions they came to. The study also includes essays, articles and interviews, which were not previously featured in reviews, in addition to, a dedication to Virilio from John Armitage and Ryan Bishop, a dedication to McLuhan from Janine Marchessault and one of Nancy's conversations with Philippe Lacoue-Labarthe. The methods of selection, systematization and cultural interpretation of the analyzed sources were used. Additionally, the biographical method was applied to establish a connection between the authors and the concepts addressed in this study. The similarities and differences of the ideas discussed were compared in the vein of a comparative approach, and the procedure for interpreting texts was based on a hermeneutic approach. As a result, it was possible to systematize the key positions of Paul Virilio, Marshall McLuhan and Jean-Luc Nancy on the evaluation and forecast for the functioning of visual images in culture. All three authors consider visual images as new and anti-proportionateto-human. Thus the axiological framework of viewing them as a cultural threat arises. Virilio stresses the antihierarchical nature of the new images, while McLuhan and Nancy emphasize their speed of dissemination and aggressiveness, respectively.